Specifics of rehabilitation of patients with the consequences of hip joint injuries after total hip arthroplasty - Filipenko, Volodymyr; Bondarenko, Stanislav; Staude, Volodymyr; Moisei, Artur; Badnaoui, Ahmed (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Postoperative rehabilitation is an integral part of the complex treatment of patients who underwent hip joint replacement. Time and methods of conducting it today are a subject of discussion among specialists. Objective: to improve the methodology for postoperative rehabilitation of patients after hip joint replacement and to evaluate its effectiveness. Methods: a prospective comparative study of the effectiveness of the developed rehabilitation technique in 25 patients (12 men and 13 women, age 22 to 79 years) with the consequences of hip joint traumatic injuries who underwent joint replacement was carried out. The control group included 25 patients (9 men, 16 women, age from 40 to 74 years) after joint replacement due to coxarthrosis caused by the transitory reactive arthritis. Selection criteria were: limb shortening more than1.5 cm, flexion contracture in hip joint, pelvic incline, pain in the area of sacroiliac joint. Rehabilitation exercises started the next day after arthroplasty by different methods and continued to be performed after discharge from the hospital. Results were evaluated after 3 months. after the surgery using the Harris and Oxford Hip Score scores. Results: in 3 months after joint replacement in the main group, the functional state of hip joint was better than in the control group: according to the Harris score — 77.2 and 72.3 points (p < 0.05), Oxford Hip Score — 36.1 and 34.4 points respectively (p < 0.05). This was achieved through the introduction of exercises for preactivation of m. erector spinae; symmetrical exercises for the balanced recovery of the frontal spine-pelvic balance and the correct stereotype of walking; active control of lumbar lordosis. Conclusions: the developed technique of rehabilitation of patients after hip joint replacement is acceptable and more effective in comparison with the currently used.